ALTER EGO DIGITAL: STUDI FENOMENOLOGIS TINDAKAN SOSIAL MAHASISWA - Rahayu Nur Faizah; Wanda Reza; Puspita Wulandari; Siti Komariah (Journal SOSIOLOGI, 2024)
This study aims to understand the dynamics of dual identity as expressed through the management of two distinct Instagram accounts representing different personalities within a single individual. This phenomenon illustrates how individuals utilize digital spaces to separate the personal and social aspects of the self in response to social expectations and the pursuit of authenticity. The research employs a qualitative approach using a phenomenological method to explore the subjective experiences of four informants who manage two accounts embodying contrasting personas. The findings reveal that the formation of dual digital identities is closely linked to two concepts from Max Weber’s theory of social action—value-rational action and instrumental-rational action. Individuals tend to use one account as a socially conforming representation of the self, while the other serves as a space for expressing personal values. These results confirm that digital spaces function not only as arenas of communication but also as new social fields that enable reflective identity negotiation. The study concludes that the creation of a digital alter ego constitutes a socio-cultural strategy for balancing external social demands with personal self-expression in the context of modern digital society.